Risk Factors for Biochemical Recurrence After PSMA-PET-Guided Definitive Radiotherapy in Patients With De Novo Lymph Node-Positive Prostate Cancer - Spohn, Simon K.B.; Birkenmaier, Viktoria; Ruf, Juri; Mix, Michael; Sigle, August; Haehl, Erik; Adebahr, Sonja; Sprave, Tanja; Gkika, Eleni; Rühle, Alexander; Nicolay, Nils H.; Kirste, Simon; et al. (Frontiers in Oncology, 2022)
Introduction The National Comprehensive Cancer Network recommends external beam radiotherapy (EBRT) combined with androgen deprivation therapy (ADT) as the preferred treatment option for newly diagnosed node-positive (cN1) prostate cancer (PCa) patients. However, implementation of positron emission tomography targeting prostate-specific membrane antigen (PSMA-PET) in the staging of primary PCa patients has a significant impact on RT treatment concepts. This study aims to evaluate outcomes and their respective risk factors on patients with PSMA-PET-based cN1 and/or cM1a PCa receiving primary RT and ADT. Methods Forty-eight patients with cN0 and/or cM1a PCa staged by [18F]PSMA-1007-PET (n = 19) or [68Ga]PSMA-11-PET (n = 29) were retrospectively included. All patients received EBRT to the pelvis ± boost to positive nodes, followed by boost to the prostate. The impact of different PET-derived characteristics such as maximum standard uptake value (SUVmax) and number of PET-positive lymph nodes on biochemical recurrence-free survival (BRFS) (Phoenix criteria) and metastasis-free survival (MFS) was determined using Kaplan–Meier and Cox proportional hazard regression analyses. Results Median follow-up was 24 months. Median initial serum prostate-specific antigen was 20.2 ng/ml (IQR 10.2–54.2). Most patients had cT stage ≥ 3 (63%) and ISUP grade ≥ 3 (85%). Median dose to the prostate, elective nodes, and PET-positive nodes was 75 Gy, 45 Gy, and 55 Gy, respectively. Ninety percent of patients received ADT with a median duration of 9 months (IQR 6–18). In univariate analysis, cM1a stage (p = 0.03), number of >2 pelvic nodes (p = 0.01), number of >1 abdominal node (p = 0.02), and SUVmax values ≥ median (8.1 g/ml for 68Ga-PSMA-11 and 7.9 g/ml for 18F-PSMA-1007) extracted from lymph nodes were significantly associated with unfavorable BRFS, but classical clinicopathological features were not. Number of >2 pelvic nodes (n = 0.03), number of >1 abdominal node (p = 0.03), and SUVmax values ≥ median extracted from lymph nodes were associated with unfavorable MFS. In multivariate analysis, number of >2 pelvic lymph nodes was significantly associated with unfavorable BRFS (HR 5.2, p = 0.01) and SUVmax values ≥ median extracted from lymph nodes had unfavorable MFS (HR 6.3, p = 0.02). Conclusion More than 2 PET-positive pelvic lymph nodes are associated with unfavorable BRFS, and high SUVmax values are associated with unfavorable MFS. Thus, the number of PET-positive lymph nodes and the SUVmax value might be relevant prognosticators to identify patients with favorable outcomes.